2020
DOI: 10.1515/npprj-2020-0038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sodium salt scaling in black liquor evaporators using existing process data

Abstract: Scaling caused by sodium carbonate and sodium sulphate salts is a common problem during black liquor evaporation and mills currently have no proper tools to monitor or follow it up. The method proposed enables automatic evaluation of scaling rates and behaviours, together with washing performance, by using measurements that are already available at most mills, such as the boiling point elevation and the overall heat transfer coefficient. The method identified the scaling correctly in most cases, normally >9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Thus, the physical mechanism prevailing in moisture transfer of the black liquor sample has resulted in a falling rate period (FRP) and internal diffusion throughout the evaporation process. Moreover, other studies also have reported similar behaviour (Karlsson, 2020).…”
Section: Analysis Of Evaporation Curves and Model Fittingsupporting
confidence: 61%
“…Thus, the physical mechanism prevailing in moisture transfer of the black liquor sample has resulted in a falling rate period (FRP) and internal diffusion throughout the evaporation process. Moreover, other studies also have reported similar behaviour (Karlsson, 2020).…”
Section: Analysis Of Evaporation Curves and Model Fittingsupporting
confidence: 61%
“…The amount of additive used in the experiments corresponds to the amount of brine added to the evaporator in Mill 1; depending on the salt content of the liquor, the amount of ash added and the crystallizing species, it might then be close to the limit required to achieve inhibition. The scaling in Effect 1C in this mill, operating at around 60 % DS, was investigated by Karlsson (2020): scaling generally disappeared when brine was added, but there were also periods when there was no inhibiting effect. There seems to be a potential for improving the situation in the mill by increasing the addition of brine and reducing the amount of salt.…”
Section: Industrial Significancementioning
confidence: 99%